PENINGKATAN MOTIVASI DAN HASIL BELAJAR SISWA KELAS VIII 5 DALAM MATERI PEMBELAJARAN MENGGAMBAR MOTIF UKIR TRADISIONAL MINANGKABAU MELALUI PENGGUNAAN MEDIA GAMBAR DI SMP NEGERI 1 KECAMATAN SITUJUAH LIMO NAGARI - Rosdiana, Drs. Yusron Wikarya, M.Pd, Drs. Syafril R, M.Sn (Universitas Negeri Padang, 2013)
This study aimed to determine the increase in motivation and student learning outcomes with the use of media to draw a picture on the learning materials carving patterns. Classroom action research was conducted by 2 cycles with steps of planning, action, observation and reflection. Tool for collecting data through observation, field notes, questionnaires and learning outcomes. Research data obtained increase students' motivation is each cycle, the first cycle of motivation average of 3.26 and the second cycle average motivation increased byan average of 4.05. Increased motivation to learn was accompanied by increased learning outcomes in each cycle. Average learning outcomes in the first cycle andthe second cycle of 72.50 earned an average of 78.60 learning outcomes. Obtaining the results of this study showed a significant increase as a result of the actions that have been done, at the end of the second cycle of learning outcomeshas been above the KKM. Kata kunci : motivasi, hasil belajar, media gambar